2020
DOI: 10.2459/jcm.0000000000001133
|View full text |Cite
|
Sign up to set email alerts
|

Imaging predictors of incident heart failure: a systematic review and meta-analysis

Abstract: Background: Preventing the evolution of subclinical cardiac disease into overt heart failure (HF) is of paramount importance. Imaging techniques, particularly transthoracic echocardiography (TTE), are well suited to identify abnormalities in cardiac structure and function which precede the development of HF.Methods: This meta-analysis provides a comprehensive evaluation of 32 studies from 11 individual cohorts which assessed cardiac indices from TTE (63%), cardiovascular magnetic resonance (CMR; 34%), or cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 54 publications
(222 reference statements)
0
14
0
Order By: Relevance
“…In a specular fashion, a transition from HF with preserved ejection fraction to HFmrEF or from HFmrEF to HFrEF predicted a higher risk of death and/or hospitalization, 48 and a decline in LVEF was found to precede death in a large cohort of HF outpatients 49 . LVEF decrease follows LV dilation and denotes the failure of LV dilation as a compensatory mechanism to sustain systolic LV function 50 . It is then reasonable to speculate that HF therapy may cause a decrease in LV volumes and then a recovery in LV function and that patients achieving a substantial increase in LVEF (such as a change in LVEF category or an increase by more than 10 units) have also a better long‐term outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In a specular fashion, a transition from HF with preserved ejection fraction to HFmrEF or from HFmrEF to HFrEF predicted a higher risk of death and/or hospitalization, 48 and a decline in LVEF was found to precede death in a large cohort of HF outpatients 49 . LVEF decrease follows LV dilation and denotes the failure of LV dilation as a compensatory mechanism to sustain systolic LV function 50 . It is then reasonable to speculate that HF therapy may cause a decrease in LV volumes and then a recovery in LV function and that patients achieving a substantial increase in LVEF (such as a change in LVEF category or an increase by more than 10 units) have also a better long‐term outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Prior evaluations on the incidence of HF have focused on the development of symptomatic, clinical HF (Stages C and D). 13 , 40 , 41 However, with the rise in prevalence of HF there is increasing interest in HF primary prevention, with a focus on the preclinical HF stages (Stages A and B). Previous studies have shown that there is a high prevalence of preclinical HF and that these individuals have both an increased risk of developing clinical HF as well as increased mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, cardiac systolic and diastolic function and the carotid artery's elasticity are affected in CCS with a higher burden of cancer treatment, and the latter correlates with apolipoprotein abnormalities. These ultrasonographical and lipid and apolipoprotein markers are known risk-factors for future CVD in different patient populations (25)(26)(27)(28)(29), but how they predict CVD in CCS remains elusive.…”
Section: Discussionmentioning
confidence: 99%